Analisis Fungsi, Peran, dan Kategori Sintaksis pada Teks Cerita dalam Buku Ajar Bahasa Indonesia Kelas VIII SMP Kurikulum Merdeka (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
The study was created to analyze the function, role, and syntax category in the sentences in story texts used in the Indonesian language textbook for class VIII junior high school independent curriculum. The data analysis technique used in this study is a billing technique with a theoretical language approach that focuses on each of the grammatical elements in sentence formation. The data on this analysis is the function, role, and syntax category in direct sentences and indirect sentences. The data source is two-story texts entitled "Parki and Egg Allergies" and "Uncle Tom's Magic Box" of the Indonesian language textbook for class VIII junior high school independent curriculum. Research has revealed five syntax functions (subjects, predicates, objects, appendages, and references), revealed a variety of syntax roles that do not always occupy the same function (the perpetrator, activity, target, driver, status, circumstances, time, tools, locative, and result), then found ten syntactic categories (pronouns, nouns, verbs, transitive verbs, intransitive verbs, verbal phrases, nominal phrases, adjective phrases, nominal-adjective phrases, and prepositional phrases). It is hoped that more variations of syntax functions, roles, and categories based on the findings of the research conducted.